RATIFIKASI CONVENTION ON THE RIGHTS OF THE CHILD 1989 DI INDONESIA (STUDI KASUS: PEMENUHAN HAK KEWARGANEGARAAN BAGI ANAK BERKEWARGANEGARAAN GANDA DI KOTA PEKANBARU) - ', Elvira; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The state has an obligation to fulfill and protect the rights of its citizens, including the right to citizenship status. Ratification of the 1989 Convention on the Rights of the Child and ratification of Law no. 12 of 2006 provides solutions to resolve citizenship problems, including for children with dual citizenship. Limited dual citizenship status is given to children resulting from mixed marriages until they are 18 years old and must choose the citizenship of one of their parents. However, the facts show that there are still many children with dual citizenship who have not applied for citizenship elections, which is feared to result in statelessness. This research wants to know how the ratification process of the 1989 Convention On The Rights Of Child was. This research is a qualitative descriptive study that is studied at the country level of analysis and uses the Voluntary Theory (Will of the State) by involving parties directly related to children with dual citizenship such as the Riau KEMENKUMHAM Regional Office. The research strategy uses data collection techniques through primary and secondary data in the form of interviews and documentation with the aim of obtaining information in accordance with the research problem. The results of this research indicate that Accession to the 1989 Convention on the Rights of the Child implies a commitment to ensure that protective rules are reflected in relevant domestic legislation. This could mean adopting modifications to the citizenship law, which in Indonesia regarding citizenship is regulated in Law no. 12 of 2006. Indonesian regulations and policies in the field of citizenship status must uphold universal values in citizenship, namely avoiding statelessness as an effort to fulfill responsibilities towards the 1989 Convention on the Rights of the Child, especially in the field of citizenship, so that no more children are stateless ( stateless). Keywords: International Convention on the Rights of the Child 1989, Children with Dual Citizenship, Ratification, Stateless